Workplace physical activity practices in real life: a scoping review of grey literature for small- and medium-sized enterprises. (26th August 2022) - Väänänen, Ilkka; Mas-Alòs, Sebastià; Vandaele, Frank; Codina-Nadal, Anna; Matas, Sergi; Aumatell, Eva; De Clerk, Ine; Puig-Ribera, Anna
Abstract: Background: There is a need to scale-up effective physical activity (PA) programmes for small- and medium-sized enterprises (SMEs), where the uptake of PA interventions is low. Identifying real-life workplace practices in PA could contribute to a better understanding of what PA programmes might be most grounded in the 'real world'. However, there is a scarcity of evidence showing what gets done. This study aimed to identify, describe and comprehensively summarize the real-life implementations of workplace PA initiatives, particularly in Europe, as a prior step to disseminating future feasible PA practices for SMEs. Methods: A scoping review of grey literature included a systematic search in the Google advanced search platform that permuted a combination of key concepts (PA, workplace, interventions/programmes), internet domains, and search operators in six different languages (Catalan, Finnish, French, Dutch, English and Spanish) between 2015 and November 2020. The analysis process was iterative, and multiple methods were used to sort, group and categorize the initiatives. Results: There were a total of 713 real-life workplace PA initiatives from different-sized organizations identified. These were categorized into five themes: active work and living, exercise and fitness programs, management and leadership, communication and dissemination, and facilities. Finally, feature trees showing a menu for real-life workplace PA practices were implemented. Conclusions: Identifying real-life practice providing a state-of-the-art snapshot of current PA practices in workplaces, which is a starting point to better understand feasible practices in the context of small- and medium-sized workplaces.